NUTRIENT CONTENT OF RHYNCHOPHORUS PHOENICIS AND ITS APPLICATION IN COMPLEMENTARY FOOD FORMULATION - Sunday UKWO; Mfoniso UDO; Ekefre EKONG (Food and Environment Safety, 2021)
Palm weevil (Rhynchophorus phoenicis) is an edible insect that is highly exploited as food. This study investigated variability in nutritional content during three developmental stages: early larva (ESL), late larva (LSL) and adult stage (ADS) and application of early larva stage in the formulation of complementary foods from the blend of broken rice and soybean flour at different proportions: A (100:0), B (94.5:5.5), C (89.5:10:5), (85.3:14.7), E (75.5:24.5) and F (70:30). Samples were assessed for proximate and mineral content while anti-nutritional factors and sensory analysis were conducted on the complementary food samples. Standard methods of analysis were used in all determinations. Results of proximate analysis indicated protein and lipid content were significantly different (p<0.05) among the developmental stages. Higher lipid content were noted in early larva (49.59%) and late larva stage (47.06%). The early larva stage was superior in ash and energy content while adult weevil had the highest percentage of protein (36.19%), carbohydrate (9.46%), fibre (9.43%) as well as micro mineral of Zn and Fe. Proximate composition of complementary foods indicated a significant (p<0.05) increase in the values for moisture, protein, lipid, ash and fibre content as the percentage of palm weevil flour increases in the formulated food samples. The recommended dietary levels for Zn and Fe in complementary foods were met with addition of 24.5% and 30% palm weevil flour without any further fortification. Anti-nutritional factors present in all complementary food samples were within safe levels. Sensory results showed that sample E with 24.5% and sample F with 30% palm weevil flour were more acceptable in all the sensory attributes determined.